2021
DOI: 10.1002/aur.2471
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Effects of Naturalistic Developmental Behavioral Interventions: A Project AIM Meta‐analysis

Abstract: We examined the quality of evidence supporting the effects of Naturalistic Developmental Behavioral Interventions (NBDIs) for facilitating change in young children with autism. We also investigated whether effects varied as a function of specific features of the intervention, samples, and outcomes measured. Twenty‐seven studies testing the effects of NDBIs were extracted from data collected for the Autism Intervention Meta‐analysis (Project AIM), a comprehensive meta‐analysis of group design, nonpharmacologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 95 publications
(103 reference statements)
3
74
0
Order By: Relevance
“…Some, as shown in figure 7 (under naturalistic developmental behavioural interventions), have been supported by randomised controlled trials showing changes most commonly in the specific social communication behaviours taught, such as joint attention, synchrony, and social interactions. 138 General programmes of psychoeducation (eg, the More Than Words programme by Hanen) are often used as well, although evidence supporting them is more variable. 139 Direct treatments with similar approaches for very young children, usually involving a non-specialist (eg, a graduate student or a childcare worker), report a range of intensity from 1 h to 40 h a week.…”
Section: The Evidence Base For Autism Interventionsmentioning
confidence: 99%
“…Some, as shown in figure 7 (under naturalistic developmental behavioural interventions), have been supported by randomised controlled trials showing changes most commonly in the specific social communication behaviours taught, such as joint attention, synchrony, and social interactions. 138 General programmes of psychoeducation (eg, the More Than Words programme by Hanen) are often used as well, although evidence supporting them is more variable. 139 Direct treatments with similar approaches for very young children, usually involving a non-specialist (eg, a graduate student or a childcare worker), report a range of intensity from 1 h to 40 h a week.…”
Section: The Evidence Base For Autism Interventionsmentioning
confidence: 99%
“…With ongoing advances in intervention trial methodology and design, the quality challenges facing the early ASD intervention field will certainly decrease over time 113 . In addition, increasing attention toward mitigating measurement bias, in particular the challenges associated with outcome proximity and boundedness, will advance the quality of ASD early intervention evidence 35 . However, it is critical that calls for increasingly robust clinical trial methodologies are balanced with research strategies to bridge the community implementation gap in early ASD intervention, bearing in mind that there is tremendous disparity in who participates in and benefits from ASD intervention research globally.…”
Section: Discussionmentioning
confidence: 99%
“…However, methodological concerns such as small sample size, detection bias related to limited informant types and objective outcome measures, and restricted trial contexts, continue to limit the replicability and generalizability of these findings (1)(2)(3). Recent meta-analytic studies revealed empirical gaps in the prediction of differential treatment response and mechanisms through which treatments work, potentially due to limited statistical power and discrepancies in designs and reporting practices across studies (1,4).…”
Section: Introductionmentioning
confidence: 99%